Handbook of forensic sociology and psychology - Morewitz, Stephen John (Springer, 2014)
"Since their emergence as social sciences, psychology and sociology have found a natural home in the justice system. And while the term forensics often translates into CSI scenarios in the public imagination, the bulk of the work takes place in the courtroom, where lawyers, judges, and jurors rely on psychology and sociology experts for aid in decision making. The Handbook of Forensic Sociology and Psychology offers comprehensive, straightforward coverage of the impact of social science on the spectrum of civil and criminal legal issues. This unique reference guides readers through the work of professionals in both fields as expert witnesses, as consultants before and during trials, and in critiquing legal and law enforcement procedure. Offering expert insights into the making and breaking of laws, contributors analyze forensic psychology and sociology theories and methods used in areas as diverse as immigration, divorce and family, product liability, and employment and education related litigation. A range of evaluative procedures, from custody to competency, child abuse to the death penalty, is examined as well." -- Publisher's description